Nadir Echo Removal in Synthetic Aperture Radar via Waveform Diversity and Dual-Focus Postprocessing - Villano, Michelangelo; Krieger, Gerhard; Moreira, Alberto (IEEE Geoscience and Remote Sensing Letters, 2018)
Synthetic aperture radar (SAR) remote sensing allows high-resolution imaging independent of weather conditions and sunlight illumination and is, therefore, very attractive for the systematic observation of dynamic processes on the earth's surface. However, as a consequence of the pulsed operation and side-looking geometry of SAR, nadir echoes may significantly affect the SAR image quality, if the pulse repetition frequency is not conveniently constrained in the design of the SAR system. As the nadir interference constraint typically limits both the swath width and the ambiguity performance of the SAR system, the investigation of novel concepts for nadir echo removal is of great interest. This letter describes how to design an SAR system without the nadir interference constraint and how to remove (not only smear) the nadir echoes by means of waveform diversity on transmit and appropriate postprocessing. The proposed technique yields improved image quality and can be exploited in a similar manner for range ambiguity suppression with remarkable benefits for the design of novel SAR systems.
Keywords: Cyclically shifted chirps; matched filtering; nadir echo; pulse repetition frequency (PRF); range ambiguities; synthetic aperture radar (SAR); waveform diversity.